PKM Validator Desain Rumah Terapung Suku Anak dalam Karya Siswa MAN Insan Cendekia Jambi - Muhammar Khamdevi (Prodi Arsitektur Universitas Matana, 2019)
The settlement of the Anak Dalam tribe in Muara Medak - Jambi often experiences flood disasters later in each rainy season. This is the number of hills that have changed from forests to become oil palm plantations which are unable to absorb water. So that in the rainy season, this area which is a shallow swamp often gets runoff from the hills which causes flooding. MAN Insan Cendikia students try to find a home design solution for residents of the Anak Dalam Tribe at Muara Medak through R & D research with the topic: